Self-imagery and advertising effectiveness: the role of sense of presence. Issue 2 (3rd April 2023) - Jang, Wonseok (Eric); Lee, Sun Young; Asada, Akira
Abstract: The purpose of this study was to assess whether self-imagery is more effective than other-imagery, and if so, to investigate the mechanism of how self-imagery generates more increased positive responses from consumers. Furthermore, we explored the boundary conditions associated with reduced positive effects of self-imagery on consumer responses. The results of Experiment 1 suggest that self-imagery was more effective than other-imagery in generating a favorable attitude toward an advertisement and purchase intention, since it enhanced a sense of presence, and consequently, imagery engagement. However, based on the results of Experiment 2, when an advertisement evoked a sense of high-risk, self-imagery generated a less favorable attitude toward the advertisement than other-imagery due to the emotion of fear evoked by the advertisement.